Teacher Agency and Reflective Professional Development: A Sociocultural Approach to Enhancing EFL Students’ Speaking Competence in Indonesian Secondary Schools - Yerly A. Datu; Mieke Puspita (Jurnal Ragam Pengabdian, 2026)
Recent research highlights teacher agency as a key factor in improving language teaching practices. This study investigates how reflective professional development strengthens teacher agency and supports EFL students' speaking competence in Indonesian secondary schools from a sociocultural perspective. A longitudinal qualitative design was employed involving six EFL teachers and their students across three public secondary schools. Data were collected through 40 hours of classroom video recordings and 12 hours of reflective dialogue sessions over six months. The findings indicate that reflective professional development enabled teachers to critically examine their instructional practices and enhance their use of dialogic questioning, contingent scaffolding, multimodal support, and adaptive pedagogical decision-making. These changes shifted classroom interaction from teacher-centered instruction toward more dialogic participation, leading to greater student engagement, increased negotiation of meaning, and improved speaking confidence. The study proposes a sociocultural model linking reflective professional development, teacher agency, and EFL students' speaking competence, offering implications for teacher professional learning and language education.